Long-Range Decoder Skip Connections: Exploiting Multi-Context Information for Cardiac Image Segmentation - Gutierrez, Nicolas; Torres, Ricardo da Silva; Falcao, Alexandre Xavier; Kozerke, Sebastian; Schwitter, Jürg; Masci, Pier-Giorgio; Montoya, Javier (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.2019.9808, 2019)
Heart is one of the most important organs inour body and many critical diseases are associated with itsmalfunctioning. To assess heart conditions, Magnetic ResonanceImaging (MRI) has become the golden standard imaging technique, as it provides to the clinicians stacks of 2D images of theheart. The problem is that examination of these stacks of 2D data,often based on the delineation of heart structures, is tedious anderror prone due to inter and intra variability. For this reason,the investigation of fully automated methods to support heartsegmentation is of paramount importance. Most of the successfulproposed methods to this problem are based on deep-learningsolutions. Especially, the U-net has been demonstrated to be avery effective architecture. In this paper, we propose the usage oflong-range skip connections on the decoder in order to improvethe generalization of the models and also to add multi-contextinformation to refine segmentation results. We evaluate ourapproach in the ACDC and LVSC heart segmentation challenges.Performed experiments on both datasets demonstrate that ourapproach leads to an improvement between 2.0% âˆ’ 3.3% on thetotal Dice for the segmentation of the heart, when combined withtwo state-of-the-art U-net-based approaches.